PENERAPAN MODEL PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN HASIL BELAJAR MATERI PERILAKU TERPUJI PADA PELAJARAN PENDIDIKAN AGAMA ISLAM - Heriyanto Heriyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
This study aims to improve student learning outcomes on the material of commendable behavior in Grade VIIB SMP Negeri 4 Gantung Belitung Timur. This research is Classroom Action Research consisting of two cycles. Each cycle consists of 2 times meeting. The subject of this research is the students of Grade VIIB SMP Negeri 4 Gantung Belitung Timur which amounted to 33 students consisting of 16 men and 17 women. The instruments of data collection in this study are a test, observation, and discussion. After going through the learning process, the results from the end of this study shows that there is an increase both in the student learning activity and student learning outcomes. In the precycles, active students are only about 20%. Then in Cycle 1 the number of active students increased to 40% and in Cycle 2 they increased to 80%. The acquisition of student learning outcomes also experienced an increase from Precycle to Cycle 2, i.e. in the Precycle 45% of students got value above KKM, in Cycle 1 increased to 66%, then in Cycle 2 increased again to 84%. Therefore, the direct learning model has a positive impact on the process of improving student learning outcomes on the materials of commendable behavior in Grade VIIB SMP Negeri 4 Gantung.